Quasi $θ(τ_1,τ_2)$-continuous Functions (European Journal of Pure and Applied Mathematics, 2025)
Our main purpose is to introduce the concept of quasi $θ(τ_1,τ_2)$-continuous functions. Furthermore, several characterizations and some properties of quasi $θ(τ_1,τ_2)$-continuous functions are investigated.
Keywords: $τ_1τ_2$-open set; quasi $θ(τ_1,τ_2)$-continuous function